2019
DOI: 10.1016/j.isci.2019.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Interactome Based on Protein Cross-linking Interfaces Predicts Drug Targets to Limit Aggregation in Neurodegenerative Diseases

Abstract: SummaryDiagnosis of neurodegenerative diseases hinges on “seed” proteins detected in disease-specific aggregates. These inclusions contain diverse constituents, adhering through aberrant interactions that our prior data indicate are nonrandom. To define preferential protein-protein contacts mediating aggregate coalescence, we created click-chemistry reagents that cross-link neighboring proteins within human, APPSw-driven, neuroblastoma-cell aggregates. These reagents incorporate a biotinyl group to efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…For experiments with drug treatment cells were plated at 6000 cells per well in a 96-well tissue culture treated plate (Costar). Drug-treated cells and controls were stained with thioflavin-T as previously described 41 , 44 , 45 . Cells were fixed after 48-h drug exposure, and incubated in phosphate-buffered saline containing 0.1% (w/v) thioflavin-T dye, and 4′,6-diamidino-2-phenylindole (DAPI).…”
Section: Methodsmentioning
confidence: 99%
“…For experiments with drug treatment cells were plated at 6000 cells per well in a 96-well tissue culture treated plate (Costar). Drug-treated cells and controls were stained with thioflavin-T as previously described 41 , 44 , 45 . Cells were fixed after 48-h drug exposure, and incubated in phosphate-buffered saline containing 0.1% (w/v) thioflavin-T dye, and 4′,6-diamidino-2-phenylindole (DAPI).…”
Section: Methodsmentioning
confidence: 99%
“…We began with total, sarkosyl‐insoluble aggregates isolated from SY5Y‐APP Sw human neuroblastoma cells (Ayyadevara et al, 2017), a model of familial Alzheimer's disease (fAD). This work revealed a complex, non‐random structure of aggregates in which megahubs (very‐high‐connectivity hubs with ≥100 partners) and hub connectors (low‐connectivity proteins linking large hubs) contribute functionally to the assembly of large aggregates (Balasubramaniam et al, 2019). We noted marked enrichment among megahubs for large structural proteins such as titin, ankyrins 1 – 3, nesprins 1 – 3, MAP1A, and other neurofilament proteins, purely as a consequence of their size.…”
Section: Introductionmentioning
confidence: 98%
“…aggregation, Alzheimer's disease, apolipoprotein E, beta amyloid, cotranslational misfolding, DNA, endogenous viruses, functional annotation, gene ontology, neurodegeneration, nucleic acid sequence, nucleic acids, protein aggregates, proteomics, retrotransposons, RNA F I G U R E 1 The "aggregate contactome" of proteins isolated from SY5Y-APP Sw human neuroblastoma cells, an in vitro model of familial AD. The contactome was generated from proteomic data for cross-linked peptide pairs in sarkosyl-insoluble aggregates, using a modified version of X-link Identifier (Balasubramaniam et al, 2019;Du et al, 2011), requiring ≥10 spectral hits per protein observed in at least 2 of 3 replicate crosslinking experiments. Hits were normalized to hub length (amino acids in the most abundant isoform).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Aβ 42 and tau are persistently found in AD aggregates as an AD pathological hallmark. This suggests that seed constituents likely coordinate common and may also mediate preferential PPIs within aggregate interfaces in different patients, which can be traced to discover individual-specific biomarkers for blockage using aggregate dispersal therapies ( Balasubramaniam et al., 2019 ). Anti-aggregate therapeutics aim to diffuse these pathological “protein lumps” in AD and other neurological diseases.…”
Section: Untargeted Proteomics Of the Mt Protein Interactome In Rdsmentioning
confidence: 99%
“…This is followed by chemical cross-linking, tryptic digest, and LC-MS/MS analysis to detect cross-linked peptide spectra. This method has successfully revealed 506 contactome protein hubs that are involved in >7,000 interactions, with ~6,000 interactions deemed specific to the disease cell line model as opposed to the non-mutant counterpart ( Balasubramaniam et al., 2019 ), which highlights the complexity in protein aggregate compositions in AD. For illustration, we used molecular docking to predict the interaction interface between the reported interacting proteins SRSF6, Tau, and APP for the subsequent development of aggregate dispersal drugs ( Figure 3 C).…”
Section: Untargeted Proteomics Of the Mt Protein Interactome In Rdsmentioning
confidence: 99%